Design Animation Video to Learning Tajweed Science for Children - Shodiq Khalidy; Luzi Dwi Oktaviana; Suliswaningsih Suliswaningsih (Journal of Multimedia Trend and Technology, 2023)
Tajweed science is one of the sciences that is used to learn how to read the Qur'an properly and correctly. So far, learning has been done by explaining it directly when children read the Qur'an, but not all children can understand it even though it has just been explained. so that learning media are needed as a means to improve teaching and learning processes. Video is an alternative choice that can be used as a learning medium so that students are more interested in and attracted to participating in learning. Therefore, the purpose of this research is to design an animated video as a medium for learning tajwid for children using the Multimedia Development Life Cycle (MDLC) method. The results of the study concluded that, after testing by media and material experts, animated videos were very suitable for use as learning media.